Development of an electroencephalogram (EEG) amplifier for a brain-computer interface (BCI) / Phang Yoke Mun - Phang, Yoke Mun (2006)
A bipolar EEG amplifier developed specifically for use in a brain-computer interface (BCI) is described. An input stage provides very high input impedance to EEG signals. AC coupling is performed in the differential stage to prevent electrode offset voltages from saturating the amplifier when high gain is used. High CMRR is achieved without trimming or component matching. The amplifier is easily modified to amplify other biopotentials. The low power requirement of the amplifier allows it to be powered through the USB connection and is suitable for portable applications. Four amplifier channels and a DRL circuit were constructed on a board. Two channels were used for amplifying EEG and another two for amplifying EOG and EMG around the throat area for artifact rejection purposes. This amplifier board was used as part of a BCI system that enables the user to select between four prosthetic hand movements and four LEDs representing other devices.